2020
DOI: 10.1016/j.ijid.2020.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Lack of antiviral activity of darunavir against SARS-CoV-2

Abstract: Given the high need and the absence of specific antivirals for treatment of COVID-19 (the disease caused by severe acute respiratory syndrome-associated coronavirus-2 [SARS-CoV-2]), human immunodeficiency virus (HIV) protease inhibitors are being considered as therapeutic alternatives. Methods: Prezcobix/Rezolsta is a fixed-dose combination of 800 mg of the HIV protease inhibitor darunavir (DRV) and 150 mg cobicistat, a CYP3A4 inhibitor, which is indicated in combination with other antiretroviral agents for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 19 publications
2
90
0
1
Order By: Relevance
“…Overall, 15 in vitro published studies were included in the systematic review, which comprised majorly of treatments done on Vero E6 cells for viral titration, drug inhibition and cytotoxicity analyses. Nine studies were included from China, 4,5,[18][19][20][21][22][23][24] three from United States of America (USA), [25][26][27] one each from Germany, 28 Netherlands 29 and Australia. 30 There were two studies 5,20 involving the antimalarial drug on hydroxychloroquine, which had chloroquine as a positive control in both the studies.…”
Section: Results From the Systematic Review Of In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 15 in vitro published studies were included in the systematic review, which comprised majorly of treatments done on Vero E6 cells for viral titration, drug inhibition and cytotoxicity analyses. Nine studies were included from China, 4,5,[18][19][20][21][22][23][24] three from United States of America (USA), [25][26][27] one each from Germany, 28 Netherlands 29 and Australia. 30 There were two studies 5,20 involving the antimalarial drug on hydroxychloroquine, which had chloroquine as a positive control in both the studies.…”
Section: Results From the Systematic Review Of In Vitro Studiesmentioning
confidence: 99%
“…One study each involving 47D11 H2L2 antibody, 29 arbidol, 18 auranofin, 27 beta-d-N4-hydroxycytidine, 25 darunavir, 28 antibodies n3086/n3113, 24 interferon-α/interferon -β, 26 ivermectin, 30 lianhuaqingwen, 21 chloroquine, 4 lopinavir, 23 ementine hydrochloride, 23 homoharringtonine 23 and Pudilan Xiaoyan oral liquid 22 All the studies had an incubation time (hours postinfection) of treatment ranging from 24 to 72 hours on average with a median of 48 hours. Table 1 depicts the baseline characteristics of in vitro studies included in our systematic review.…”
Section: Results From the Systematic Review Of In Vitro Studiesmentioning
confidence: 99%
“…There are several ongoing clinical trials evaluating safety and efficacy of favilavir against other antivirals in China, Japan, Canada and avifavir in Russia. Darunavir/Cobicistat and Darunavir/Ritonavir [ 44 ] have also been tested in a randomized controlled trial of 30 patients in China which showed that darunavir/cobicistat was not effective in the treatment of COVID-19. There are no data from clinical trials that support the use of other HIV protease inhibitors to treat COVID-19, such as Atazanavir.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of old drugs have been clinically tested for potential e cacy against SARS-CoV-2, such as lopinavir/ritonavir, hydroxychloroquine, darunavir and cobicistat 20,21,24,25 . Although some of these molecules are effective in cellular models, clinical trials showed no signi cant improvement in symptoms and length of hospitalization 21,26 ; thus, the e cacy of these drugs remains controversial. Since the targets of these drugs on SARS-CoV-2 are unclear, the mechanism is ambiguous, which suggests that it is essential and reliable to start from a de ned target to identify candidate drugs.…”
Section: Discussionmentioning
confidence: 99%